Integrated scheduling of intermodal transportation with seaborne arrival uncertainty and carbon emission. (November 2020) - Wang, Wenyuan; Xu, Xinglu; Jiang, Ying; Xu, Yunzhuo; Cao, Zhen; Liu, Suri
Highlight: A port-centric supply chain (PCSC) covers production and intermodal transportation. An integrated scheduling (IS) model with seaborne uncertainty and carbon emission. An IS method to balance system cost evaluation and carbon emission. An improved multiple heterogeneous coding genetic algorithm for IS study. A cost-effective system support tool for identifying resource bottleneck in a PCSC. Abstract: The world trade globalization process has triggered growing attention to port-centric supply chain (PCSC) management, wherein the land transport and maritime transport are connected by ports. Modern scheduling plans for PCSC should put more emphasis on intermodal transportation to achieve an effective and environmental-friendly management scheme. Therefore, this paper proposes an integrated scheduling model with an improved multiple heterogeneous coding genetic algorithm for PCSC management, wherein the intermodal transportation has been investigated under seaborne uncertainties. By analyzing the overall cost and carbon emission under different operational strategies, the effects and countermeasures of integrated scheduling on system optimization and carbon emission mitigation policy in PCSC are discussed. The results of case studies based on a departure port in Southeast China indicate that the integrated scheduling method proposed can significantly decrease the overall system cost and carbon emission. Moreover, suggestions on optimal resource allocation and carbon emission reduction are proposed.